Indication of the color change on the oxidation properties of fragrant rapeseed oil during shelf storage - Li, Qi (2023)
The cause and trend of color change and their links to oxidative properties were investigated by simulating shelf storage conditions for fragrant rapeseed oils (FROs). Under illumination, the L* value gradually increased with the storage time. The a* and b* values showed different trends depending on brands. The photodegradation rates of chlorophylls were 8.6 ∼ 15 times higher than those of carotenoids. The change in color of FROs was mainly caused by the light-induced photodegradation of chlorophyll. Compared with the hydroperoxides, the contents of some secondary oxidation products [i.e., 2-butenal, octane, (Z)-2-octene, 2,4-octadiene, (Z)-2-heptenal, (E, E)-2,4-heptadienal, and (E)-2-decenal] were more closely associated with the color variation with correlation coefficients of 0.6 ∼ 0.94. Significant negative correlation was found between α-tocopherol content and oil color difference. Therefore, illumination was the main reason for the color degradation of the FROs. The varying degree of color difference was strongly linked to the quality deterioration caused by oxidation.